Teoría de los juegos y su aplicación a los negocios internacionales: acuerdo comercial Unión Europea-Ecuador en el sector agrícola bananero - Jimenez Cabrera, Jackson Honorio (2018)
Bananas in Ecuador represent 10 % of total export; and it is the second largest export item. The adequate quality and good taste of Ecuadorian bananas has allowed Ecuador to position itself internationally as one of the largest exporters, since its fruit comes mostly to importing countries, especially the European market, allowing you opportunities to make commercial agreements. However, the international trade negotiations of Ecuadorian bananas have not been an easy subject; its edges have been surrounded by infinity of interests, conflicts and legal disputes, which in some cases has generated commercial disadvantages in discriminatory conditions. Through the theory of game, the aim is to analyze the conflicts, trying to identify the causes of the conflicts, the strategies of the players, the result achieved and making assertive decisions in the future scenarios of commercial policies in the chess of the economy world.